Development of the methodology “What If” and its impact on knowledge management as a strategy to improve quality in education - Zambrano Valdivieso, Oscar Javier (2017)
The article analyzes the impact of the development of the methodology What If? onknowledge management as a strategy to improve the quality of education, in which specificinformation of a process is used, such as the Process Flow Diagram (PFD), Pipingand Instrumentation Diagram (P&TI), to generate a kind of checklist questions. MattMurrie (2016) proposed the methodology; it has had a positive impact on the school environmentwhen allowing teachers and students to question themselves about the form orthe sense in which the daily activities are accomplished. Teachers are invited to becomefacilitators who guide, design, organize and evaluate the results of the learning strategies.This methodology opens new channels of communication for different sectors workingon knowledge management.